The public sphere today: Places, logics and expectations - Rabotnikof, Nora (2008)
The following work offers a reflection on how the public sphere has been redefined. These reflections are considered within the parameters of the transformations that have taken place in the relationship between the State and civil society. The article begins by looking at some of the academic and political discourses that expressed the need to strengthen the public space. This point of departure emphasizes the need to clarify the definition of public space, as well as the need to demystify the complex matrix of forces that underlie the discourses in question. Needless to say, this work does not pretend to bind the debate to traditional definitions, but rather to understand how such ambivalence and misunderstandings have come to feature in the strategies adopted by political and social actors. Without attempting to undergo a rigorous conceptual history, this work analyzes the transformation of the state-public sphere into the state-social sphere, concluding with some brief comments on the innovations that have accompanied the “return of the State”.